ANALISIS ALIH FUNGSI LAHAN DAN IMPLIKASINYA TERHADAP KETERSEDIAAN PANGAN DI KECAMATAN KLATEN SELATAN KABUPATEN KLATEN - Artika Kusumawardani; Vini Arumsari; Budi Widayanto (Jurnal Dinamika Sosial Ekonomi, 2015)
Agricultural land conversion is one of the phenomenon of change agricultural land into non agriculture. The aims of this study was to determine the effect of factors including age, education level, family dependents, land ownership, and income on farmer's decision in converting agricultural land and the Agricultural land conversion impact on food availability This study uses a description approach using Chi Square analysis in analyzing factors that influence farmers' decisions to convert agricultural land into non-agricultural land, and analysis of Carrying Capacity Rescue / CCR in analyzing the impact of the conversion of agricultural land to food availability in the Southern District of Klaten. Land conversion does not affect the availability of food in the Southern District of Klaten. From the test results of Carrying Capacity Rescue / CCR showed a value of 1.10> I therefore, the Southern District of Klaten still have the ability to support the basic needs of the population. There is a correlation between the characteristics of the decision-making of farmers to convert land. there is a real relationship between the age of respondents with land conversion, with a probability value of 0.009 the value is less than 0.05 (a= 0.05), there is a relationship between the area of land owned by farmers with land conversion, ie the probability value of 0.035 the value is less than 0.05 (a=0.05)Key words: factors, land use change, food availability